Proyeksi Permintaan Dan Penentuan Ukuran Batch Optimum Produk Pada Agroindustri (Studi Kasus di Industri Jamu) - Iveline Anne Marie (JURNAL TEKNIK INDUSTRI, 2011)
The era of globalization requires the industry to create competitive advantage. One of the factors that affect competitive advantage, which tend to be controlled is the internal factors of the company / industry, the factors concerning the performance of inputs (resources used to produce the output), the performance of the process and the performance of output (products / outputs of the process). In order for a company / industry excels in the competition, it takes a model of demand forecasting and aggregate production planning model to help companies / industry in planning its production activities. For the purpose of this study was to determine the projected demand for products and to know the optimum batch size for each item of products in order to meet the needs of the operational planning of production.With the acquisition of the projected demand for products and optimum batch sizes for each product item, the next company can perform various calculations for the needs of enterprise production planning so as to improve the performance of the process input or output of production, and excel in the competitive industry.